2018
DOI: 10.1186/s13633-018-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flash Glucose Monitoring in children with Congenital Hyperinsulinism; first report on accuracy and patient experience

Abstract: BackgroundThe factory calibrated FreeStyle Libre (FSL) flash glucose monitoring system has been recently introduced for use in patients with diabetes mellitus. There are no reports available regarding its use in patients with congenital hyperinsulinism (CHI). We have assessed the accuracy of FSL compared to the finger prick capillary blood glucose (CBG) over 2 weeks period in patients with CHI and evaluated the parents’ experience of using FSL.MethodsFour hundred sixty-seven episodes of CBG along with correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 15 publications
5
17
0
Order By: Relevance
“…Several studies have reported an overall performance of the FL comparable to that of other state-of-the-art CGM systems [7,20,21,22,23,24,25,26,27,28,29]. Our main results are in line with previous observations as we find an overall MARD of 12.3% and half of the participants having a MARD at or below 10%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have reported an overall performance of the FL comparable to that of other state-of-the-art CGM systems [7,20,21,22,23,24,25,26,27,28,29]. Our main results are in line with previous observations as we find an overall MARD of 12.3% and half of the participants having a MARD at or below 10%.…”
Section: Discussionsupporting
confidence: 91%
“…Several of the previous FL performance studies also report individual MARDs, where some are as large as we observed in our study [7,22,27]. The studies by Ólafsdóttir et al [21] and Alsaffar et al [24] report a bias in the measurements, but on an overall level only. To the best of our knowledge, the present study is the first to report on individual bias and lag issues as reasons for the high variation in individual MARDs in FL.…”
Section: Discussionsupporting
confidence: 67%
“…CGM measures interstitial glucose concentrations indicating the direction, magnitude, frequency, duration and causes of fluctuations in these. There is now a study on its accuracy in children with HH [ 93 ], as this can significantly improve the quality of life of these patients.…”
Section: Diagnostic Investigations Of Hhmentioning
confidence: 99%
“…There is now more research of use of CGM in children with HH which might help to detect early hypoglycemia leading to prompt management [ 93 ]. There have been reports of pitfalls of 18F-DOPA PET-CT in accurately detecting focal lesions in CHH [ 106 , 173 ].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Caregivers found the indication of glucose trends to be helpful, felt more confident in everyday management of the condition, and felt less worried about the occurrence of asymptomatic hypoglycemia [ 12 , 14 ]. However, older rtCGM/isCGM systems were reported to have limited accuracy, especially for hypoglycemic levels, and therefore not recommended to completely replace capillary blood glucose (CBG) testing, but rather seen as an adjunctive, beneficial therapy [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%